Market structure and market performance in e-commerce - Franz Hackl; Michael E. Kummer; Rudolf Winter-Ebmer; Christine Zulehner (Institute for Advanced Studies (IHS), 2012)
We investigate the causal effect of market structure on market performance in the consumer electronics. We combine data from Austria's largest online site for price comparisons with retail data on wholesale prices provided by a major hardware producer for consumer electronics. We observe input prices of firms, and all their moves in the entry and the pricing game over the whole product lifecycle. Using this information for 70 digital cameras, we generate instrumental variables for the number of firms in the market based on the shops' entry decisions on other product markets in the past. We find that instrumenting is particularly important for estimating the effect of competition on the markup of the price leader.
Keywords: L11; L13; L81; D43; 330; retailing; product lifecycle; market structure; market performance; markup; price dispersion